RANCANG BANGUN PENGATURAN RUANG MEETING DENGAN ALGORITMA DIVIDE AND CONQUER PADA HOTEL AMALIA BANDAR LAMPUNG - Susilo Wahyu; Sulyono -; Rio Kurniawan (IIB Darmajaya, 2019)
Recording of meeting rooms is carried out by the Amalia Hotel marketing division by using calendar events and this takes a long time. The marketing division wants an application that is able to analyze meeting room packages that are ordered most quickly and accurately. To determine the meeting package that is most ordered at Amalia Hotel, the marketing division requires several criteria including the usage period, the name of the meeting room and meeting package. The divide and conquer method is applied by way of dividing the data of the use of meeting packages into two groups, determining the greatest value of each group, and combining the largest values of each group together to find the greatest value.The application applied is in accordance with the needs of the marketing division. Evidently when looking for packages that are most ordered from 140 data borrowing meeting packages, the application can display the percentage of meeting packages that are the most in order within 0.0018 ms. Applications can be developed using other sorting methods such as bubble sort and selection sort that can solve problems without dividing the problem into two groups first. Keywords: Application, Meeting Room, Meeting Room Package